The relationship between macroeconomic volatility and the stock market volatility: Empirical evidence from Pakistan - Muhammad Irfan Javaid Attari; Luqman Safdar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
The relationships among the macroeconomic variables and stock returns analyzed in both the developed and developing countries, but are not well estimated in Pakistan. The current study explores the time series as analysis of economic variables and stock market by applying the Exponential Generalized Autoregressive Conditional Heteroskedasticity (EGARCH). The macroeconomic variables include interest rate, inflation, and gross domestic product. For representation of stock market, Karachi Stock Exchange (KSE-100 Index) is taken as test market. The monthly data of the variables for the time period from December 1991 to August 2012 is used for the current study analysis. The ADF and ARCH tests are used to check the stationarity and homoskedasticity in the data respectively. The results show that macroeconomic variables have substantial influence on the stock prices. The stock prices have much impact on the economy of the country, and are consider as the best indicators for future prediction of the market and economy as well. Furthermore, the stock market in Pakistan is highly volatile the regulatory bodies must pay attention to make it less volatile.
Keywords: 330; Stock market volatility; macroeconomic volatility; EGARCH; KSE